2000
DOI: 10.1016/s0896-6273(00)00124-0
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Transport of Amyloid Precursor Protein Is Mediated by Direct Binding to the Kinesin Light Chain Subunit of Kinesin-I

Abstract: We analyzed the mechanism of axonal transport of the amyloid precursor protein (APP), which plays a major role in the development of Alzheimer's disease. Coimmunoprecipitation, sucrose gradient, and direct in vitro binding demonstrated that APP forms a complex with the microtubule motor, conventional kinesin (kinesin-I), by binding directly to the TPR domain of the kinesin light chain (KLC) subunit. The estimated apparent Kd for binding is 15-20 nM, with a binding stoichiometry of two APP per KLC. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
393
5
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(416 citation statements)
references
References 60 publications
14
393
5
1
Order By: Relevance
“…33,34 Our time-lapse study, however, revealed that both cargoes were affected by defective anterograde axonal transport when JSAP1 and JLP were ablated (Figures 4a-d), and that these defects were reversed by exogenously expressed WT JSAP1 or JLP, but not by ΔKBD-mutant JSAP1 or JLP (Figure 5b; Supplementary Figure S5b). In addition, expressing JSAP1-LZ, a JSAP1 mutant that is unable to interact with KLC, almost completely rescued the impairment of anterograde axonal APP and mitochondrial transport (Figure 5b).…”
Section: Discussionmentioning
confidence: 91%
“…33,34 Our time-lapse study, however, revealed that both cargoes were affected by defective anterograde axonal transport when JSAP1 and JLP were ablated (Figures 4a-d), and that these defects were reversed by exogenously expressed WT JSAP1 or JLP, but not by ΔKBD-mutant JSAP1 or JLP (Figure 5b; Supplementary Figure S5b). In addition, expressing JSAP1-LZ, a JSAP1 mutant that is unable to interact with KLC, almost completely rescued the impairment of anterograde axonal APP and mitochondrial transport (Figure 5b).…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport. The observation that AbPP can serve as a kinesin cargo receptor (Kamal et al, 2000(Kamal et al, , 2001 as well as the inhibition of kinesin-dependent transport by tau overexpression (Ebneth et al, 1998;Stamer et al, 2002) should not be overlooked. It would be interesting to see whether tau overexpression and Al affect intracellular transport via a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The binding interaction was mapped to amino acids 867-894 of US11 and the heptad repeat cargobinding domain of kinesin. Satpute-Krishnan et al also showed that amyloid precursor protein, a putative kinesin receptor, 121,122 associates with viral particles during anterograde transport. Similar to retrograde movement, data are accumulating that HSV nucleocapsids and tegument travel separately from envelope components in anterograde transport.…”
Section: Virus Attachment and Entrymentioning
confidence: 98%